Conservation history, hunting policies and practices in the South Western Mozambique borderland in the 20th century - Jose, Paulo Lopes (My University, 2017)
This study uses both primary and secondary sources to investigate the history of the communities living in the southern Mozambique hinterland in the 20th century. It specifically examines the evolution of the colonial hunting laws and the establishment of hunting reserves in southern Mozambique. In this thesis, I argue that the Portuguese colonial administration put little effort into the protection of fauna and ecosystems in the south western Mozambique hinterland. Portuguese hunting laws were issued to provide the colonial system with revenue – through a system of fees imposed on licensed hunters when entering Mozambican forests and hunting reserves – rather than to improve fauna management. Colonial laws (particularly fees for the hunting permits) made it difficult for the majority of local African peasants to access game resources, on which during periods of drought and lack of foodstuffs they depended for subsistence. The study explores the extent to which postcolonial development projects affected conservation and the livelihoods of communities living in conservation areas. It shows how the period following independence was also characterised by mass killing of wildlife. In 1978, as part of the construction of the Massingir dam, Frelimo government officials relocated families living along the Elephants valley to areas having poor soils in Coutada 16, thus reducing the ability of the cultivators to produce enough food to sustain their families. Lack of food supplies increased the dependence of local families on bush meat for food. The armed conflict, which broke out immediately after independence in 1975 and lasted until 1992, contributed to the mass killing of wildlife, as both government soldiers and RENAMO fighters exploited bush for food. The end of the armed conflict allowed the Government of Mozambique (GoM) to implement projects aimed at rehabilitating the ecosystems destroyed by war and the transformation of Coutada 16 into the Limpopo National Park (LNP) in 2001. In 2002, the integration of the LNP into the Great Limpopo Transfrontier Park (GLTP) turned into reality Hertzog´s 1927 desire to create a transnational conservation area across the South Africa – Mozambique border.
A thesis submitted to the Faculty of Humanities of the University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Doctor of Philosophy in History, August 2017
Keywords: Conservation of natural resources--Mozambique--History--20th century; Conservation of natural resources--Mozambique--Citizen participation; Wildlife conservation--Economic aspects--Mozambique